Prevalence of self-medication practices and its associated factors in Urban Puducherry, India - Selvaraj, Kalaiselvi (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND AND OBJECTIVES: Self medication is an important concern for health authorities at global level. This study was aimed to find the prevalence of self medication for allopathic drugs and associated factors among households of urban community. This study was also aimed at assessing the attitude of respondents who had experienced self-medication. MATERIALS AND METHODS: This cross-sectional study was done in field practice area attached to a medical institution in urban Puducherry. A total of 352 subjects from 124 households were selected by random sampling. With pretested interview schedule, information regarding self-medication use in the past three months and associated sociodemographic factors, purpose, source of drug procurement, attitude toward self-medication use were collected. RESULTS: Prevalence of self-medication was found to be 11.9%. Males, age >40 years and involving in moderate level activity of occupation, were found to be significantly associated with higher self-medication usage (P < 0.05). Fever (31%), headache (19%), and abdominal pain (16.7%) are most common illnesses where self-medication is being used. Telling the symptoms to pharmacist (38.1%) was the commonest method adopted to procure drugs by the users. Majority of the self-medication users expressed that self-medication is harmless (66.6%) and they are going to use (90%) and advice others also (73.8%) to use self-medication drugs. CONCLUSION: Self-medication is an important health issue in this area. Health education of the public and regulation of pharmacies may help in limiting the self-medication practices.